2016
DOI: 10.1007/s13197-016-2287-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cooking method (grilling, roasting, frying and sous-vide) on the oxidation of thiols, tryptophan, alkaline amino acids and protein cross-linking in jerky chicken

Abstract: Broiler breast (pectoralis major) meat was submitted to salting with NaCl ? NaNO 3 followed by a drying process to produce jerky-type chicken. The final product (raw broiler charqui) was desalted and then cooked using grilled, roasted, fried and sous-vide techniques. Sous-vide cooked samples showed lowest results of moisture loss compared to roasted and fried ones. Fatty acid profile suffered minor changes after cooking of broiler charqui. Regarding to protein oxidation, tryptophan fluorescence, protein carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 39 publications
1
33
2
Order By: Relevance
“…In contrast to our hypothesis that protein breakdown would be accelerated with SV, AA indicators of protein breakdown, such as collagen breakdown, including hydroxyproline, did not appear at different rates in circulation. This was surprising given that previous studies had demonstrated that longer periods of cooking solubilise the connective tissues, decrease hardness and make the denatured protein more accessible to digestive enzymes [8,29]. However, in our study, the comparatively lower collagen content of the sampled beef cut [30] prevented our ability to draw firm conclusions.…”
Section: Discussioncontrasting
confidence: 62%
“…In contrast to our hypothesis that protein breakdown would be accelerated with SV, AA indicators of protein breakdown, such as collagen breakdown, including hydroxyproline, did not appear at different rates in circulation. This was surprising given that previous studies had demonstrated that longer periods of cooking solubilise the connective tissues, decrease hardness and make the denatured protein more accessible to digestive enzymes [8,29]. However, in our study, the comparatively lower collagen content of the sampled beef cut [30] prevented our ability to draw firm conclusions.…”
Section: Discussioncontrasting
confidence: 62%
“…During oxidative reactions, meat proteins may be attacked directly or indirectly, by reactive oxygen species (ROS) or by‐products from lipid oxidation, respectively (Soladoye et al ., ). These reactions cause changes in the amino acid side chains and the peptide chain, which can lead to protein fragmentation, reticulation, conformational changes, altered susceptibility to proteolytic enzymes, tryptophan losses, increases on carbonyl compounds and formation of protein cross‐linking (Utrera et al ., ; Chen et al ., ; Silva et al ., ). Understanding how these severe chemical modifications impact on particular meat quality traits has been one major challenge to food scientists over the last 15 years.…”
Section: Discussionmentioning
confidence: 97%
“…An asterisk on top of a bar at a particular processing stage denotes significant differences (P < 0.05) between that processing stage and the immediately previous one within a particular cooking method. increases on carbonyl compounds and formation of protein cross-linking (Utrera et al, 2012;Chen et al, 2013;Silva et al, 2016). Understanding how these severe chemical modifications impact on particular meat quality traits has been one major challenge to food scientists over the last 15 years.…”
Section: Impact Of Protein Oxidation On Nutritional Value Of Readyto-mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of grilling, roasting, frying and sous-vide techniques, the last one seems to be the most advantageous cooking methods to obtain high-quality meat devoid of protein carbonylation and disulfide bond formation. Free thiol groups, Schiff base formation and hardness are impacted by the length of the cooking [9] .…”
Section: The Effect Of Oxidative Stressmentioning
confidence: 99%